Menjaga Keaslian dan Kesakralan Situs Candi Jolotundo Trawas, Mojokerto - Miftakhul Khoiroh Nor Derisma (Universitas Muhammadiyah Surabaya, 2024)
The Jolotundo Temple site in Trawas, Mojokerto, is one of the cultural heritages that has high historical and spiritual value. This temple is often used as a place of meditation and worship which is equipped with ornaments and reliefs that depict various aspects of the beliefs and cultures that are adhered to. In addition, the temple also has an important architectural and historical value. So this article explains to identify efforts to maintain the authenticity and sacredness of the Jolotundo Temple site amidst the pressures of modernization and tourism. The method used is a qualitative method and data collection is carried out by means of observation and interviews. The results of the study show that efforts have been made in several stages, including in environmental management, preservation of artifacts, and educational programs by collaborating between the government and the community. However, challenges still exist, such as increasing visitors and lack of awareness of cultural values. Therefore, it is advisable to frequently monitor and evaluate improvements in visitor management to find the right solution.